Discussion about math, puzzles, games and fun. Useful symbols: ÷ × ½ √ ∞ ≠ ≤ ≥ ≈ ⇒ ± ∈ Δ θ ∴ ∑ ∫ π -¹ ² ³ °

You are not logged in.

- Topics: Active | Unanswered

Pages: **1**

**Jerre****Guest**

Hello,

I have to proof a formula for recursively calculating the least squares.

In my proof, I have the formula (A' A)^(-1)

(where ' means transpose)

How do I eliminate the inverse? Has somebody a hint of a Theorem to use?

Many thanks in advance,

Jerre

**George,Y****Member**- Registered: 2006-03-12
- Posts: 1,306

You don't have to

You can point out A'A= (A'A)'

and (A'A)[sup]-1[/sup]= [(A'A)[sup]-1[/sup]]',

which need each theorems to prove.

In addition, there is no way to eliminate (A' A)^(-1) generally, and the final formula involves it.

*Last edited by George,Y (2006-11-10 17:16:12)*

**X'(y-Xβ)=0**

Offline

Pages: **1**